Model Penyebaran Penyakit Polio Dengan Pengaruh Vaksinasi - Ma’rifatun, RR Laila; Sugiyanto, Mr. (UIN Sunan Kalijaga Yogyakarta, 2013)
Polio (Poliomielitis) is an infectious disease caused by the polio virus. This disease attacks the entire body (including the muscles and nerves) and can lead to muscle weakness that is permanent, paralysis or death. This paper will discuss on the influence of vaccination against polio disease spread in the human population that settled in the form of mathematical modeling.